EVALUATION OF INITIAL GAS VOLUME OF COALBED METHANE USING FOUR METHOD - Heri Susanto; Karen Sondakh; Ratnayu Sitaresmi; Ryodi Hananda (Journal of Mechanical Engineering and Mechatronics, 2018)
Coal bed methane (CBM) is an unconventional energy resources in which the main ingredient is methane gas formed in the process of formation of coal (coalification). Based on research Advance Resource International inc. (ARI), the CBM resource potential is 453 Tcf spread across 11 basins in Indonesia. CBM technology is expected to be one of the alternative energy can play a role in helping to suppress the natural gas needs of oil as one of the energy commodities di Indonesia.This paper discusses about a calculated initial volume of gas in place (Gas in Place) on CBM reservoir “X” field. This initial gas volume calculation first calculating the gas content is becoming an important parameter in calculating the initial volume. This content gas value can be obtained through data analysis proximate such as ash content, moisture content, volatile matter, fixed carbon which such data can be obtained from laboratory results. But there is also the calculation of the gas content which can be obtained by simply using coal density data using several methods of calculation, such as the Mavor method, Bambang, Modified Kim, and Mullen method. In the “X” field there are five wells coalbed methane drilling has been done, namely, SS-1, SS-2, SS 3, SS-4 and SS-5 and there are five layers are seam-1, seam-2, seam-3, seam-4, and seam-5. Based on the calculations were also obtained in the “X” field coal rank, the average is sub-bitminous. Of the five wells will be calculated gas content and the initial volume of gas using a method Mavor, Bambang, Modified Kim, and Mullen.Using four methods then the gas content in the SS well ranged between 200-500 SCF / ton. And assuming that the well drainage area (A) covering an area of 100 acres, the obtained large volumes of coal bed methane wells SS-1 with the four methods ranged from 3-9 BSCF, the SS-2 ranged between 1-3 BSCF, wells SS- 3 are 2-5 BSCF, the SS-4 range between 1-3 BSCF and the SS-5 ranges between 1-3 BSCF.We will be compared the initial gas volume in the Field “X” using the four methods with data from the laboratory result. From that analysis it can be proved that the Bambang method is the most suitable method and represents CBM field in Indonesia. So the initial gas volume in Field “X” is using the result from Bambang method, and the result are 5312.17 MMscf on the SS-1well, 2385.77 MMscf on the SS-2 well, 3330.84 MMscf on the SS-3 well, 1635.44 MMscf on the SS-4 well, and 1608.74 MMscf on the SS-5 well. And the total initial gas volume in the “X” Field is 14273 MMSCF.